Home based obstetric care: How much safer? - Joshi, Manohar (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Objective: To find out the obstetric care management and the consequences of home based delivery assisted by skilled birth attendants or quacks from registered delivery of referral cases in Bhim Hospital, Siddharthnagar, Rupandehi district, Nepal. Methods: This is a retrospective and descriptive study of the clients who were referred to and from Bhim Hospital, Siddharthnagar for obstetric conditions during the past four years (2058-2061). Results: A total number of 3174 women were cared during these 4 years (2058-2061). A decreasing tendency in hospital deliveries were noted during the same period of four years (2058-2061). The numbers of cases being referred from the community were seen to increase every year from 4.6% in the first years to 19.8% in the fourth year. Out of the 380 cases referred 188 were complicated obstetric cases. Among them 48 women were delivered by ventouse while 140 women had to be re-referred for operative delivery to district hospital having caesarean facility. This was shear wastage of time. Holding back the laboring women in villages for the benefit of incentive; provided by Government to promote home based delivery care was speculated to be one of the reasons why women were brought so late. Conclusion. In view of women's benefit and to limit unnecessary dilly-dallying in between, it is rather better to refer difficult obstetric case from the community directly to the district hospitals, equipped with extended comprehensive emergency obstetric care (CEOC) services, escaping various ladders of referral thus saving time. Instead a concept of birthing center to be emphasized more than home based delivery. Keywords: Birthing center, extended CEOC services, ventouse delivery in the community. doi:10.3126/njog.v2i1.1471 N. J. Obstet. Gynaecol Vol. 2, No. 1, p. 20 - 22 May -June 2007